FORMS OF WORK OF FOREIGN GOVERNMENTS ON INVOLVEMENT IN NATIONAL SCIENCE HIGHLY QUALIFIED PERSONNEL - V. A. Tsibikov (Вестник университета)
The results of data analysis on changes in the number of Russian research and teaching staff due to increased international competition for highly qualified personnel have been given. The main trend of the process is the decrease in their total number from 2015 to 2018 by an average of 900-1000 people annually, which exceeds similar indicators among other categories of the Russian population. The experience of the state bodies of the leading world powers in applying forms of work to create conditions for attracting foreign scientists to research and educational activities in the national interest has been analysed: a) improving the structure and powers of state bodies responsible for attracting scientists to the country; b) developing and implementing state target programs; c) improving national regulations for granting work visas to foreign scientists by simplifying administrative procedures. It has been concluded that it is necessary to monitor emigration processes among highly qualified personnel in Russia and make it personalized. The need for a point analysis of the reasons and conditions that contribute to the decision of a representative of the scientific and pedagogical community to move to another country has been substantiated.